PENGEMBANGAN MEDIA E-KOMIK UNTUK MEMBENTUK KARAKTER PEDULI LINGKUNGAN PADA PEMBELAJARAN IPAS KELAS V DI SDN PASAREAN 02 PAMIJAHAN BOGOR - Rusydi, Lina Najwatur; Hidayah, Iin Inarotul; Mukri, Rusdiono (Prodi PGMI IAI Sahid, 2026)
This study aims to develop an e-comic learning medium to foster environmental awareness in fifth-grade students during science lessons at SDN Pasarean 02 Pamijahan, Bogor. The background of the study was low student environmental awareness and the lack of use of innovative learning media. The method used was Research and Development (R&D) with the ADDIE model. Validation results by material, media, and language experts indicated that the e-comic was highly valid. Implementation of this medium significantly impacted the development of environmental awareness, as demonstrated by an increase in scores from pretest to posttest and a Paired Sample t-test with a significance level of 0.000 < 0.01. Teacher and student responses indicated that the e-comic was useful, engaging, and easy to understand. This e-comic is expected to serve as a reference in the development of other innovative learning media.